Urban planning for biodiversity: An assessment of green plans in Northern Italy - Lazzarini, Luca; Mahmoud, Israa; Pastore, Maria Chiara (TeMA - Journal of Land Use, Mobility and Environment, 2024)
In the latest debate on the urban planning-biodiversity nexus, a forefront attention is given to the possibility to embrace goals, targets, and indicators from the global, European, and national levels and to apply them at the local scale through targeted policies and specific actions. This article proposes an attempt to identify a theoretical framework for the integration of biodiversity in spatial planning processes at different scales, through mainstreaming ecological transition, rightsizing the strategies and policies for biodiversity recovering, and downscaling the different challenges in the local contexts. Afterward, a sample of Green Plans and Strategies from the Italian domestic context is analyzed across a deducted analytical framework including four dimensions: biodiversity goals, targets, commitment to implementation, and public participation. Results from the analysis emphasize the focus of the green plans generally oriented to conserve existing biodiverse urban areas rather than radically igniting new possibilities in spaces where biodiversity can be restored, or it is already present but not perceived by local communities. Lastly, the article highlights four gaps characterizing the biodiversity-planning nexus, in its theoretical and operational implications.